Impact of job resources on organizational citizenship behavior among primary care staff in Guangzhou, China: a cross-sectional study - Liying Fan; Jiamin Yang; Qiao Hou; Shanshan Feng; Shanshan Feng; Aiyun Chen; Aiyun Chen; Lingzhi Han (Frontiers in Public Health)
BackgroundLow motivation to work among primary care staff is the key hindrance to the development of primary healthcare. Job resources are a kind of tool that helps employees achieve their work objectives and an internal motivating factor that generates positive behavior. This study investigates the impact of job resources on organizational citizenship behavior (OCB) among primary care staff and the moderating effect of demands-abilities fit on this relationship. The ultimate goal is to improve primary care staff’s OCB levels and stimulate their motivation at work to provide policy suggestions.MethodsTaking Guangzhou City in southern China as the research site, this cross-sectional study selected 600 primary care staff using the multi-stage stratified random sampling method. The job resource scale, OCB scale, and demands-abilities fit scale were used as research instruments. Data were collected from September to November 2019 using a self-filling method. The multiple linear regression method was used to analyze the influence of job resources on OCB. The hierarchical multiple regression analysis was used to examine the moderating effect of demands-abilities fit.ResultsOverall, 512 effective questionnaires were completed, with a recovery rate of 85.3%. Multiple linear regression analysis, after controlling for socio-demographic factors, shows job resources (β = 0.489, p < 0.001) and three dimensions of job resources: Social support (β = 0.175, p < 0.01), job control (β = 0.177, p < 0.01), and possibilities for professional development (β = 0.203, p < 0.001) had a positive predictive effect on OCB. Demands-abilities fit moderated the positive predictive effects of job resources (β = 0.095, p < 0.01), social support (β = 0.077, p < 0.05), job control (β = 0.102, p < 0.01), and possibilities for professional development (β = 0.113, p < 0.01) on OCB.ConclusionThe findings demonstrated that the higher the level of job resources perceived by primary care staff, the higher the OCB; furthermore, the demands-abilities fit enhances the positive effect of job resources on OCB. It is suggested that primary healthcare institutions should prioritize creating an organizational atmosphere of interpersonal support, appropriately ensure the autonomy of primary care staff in their work, and pay attention to the needs of professional development and ability improvement. These measures may improve the OCB of primary care staff, stimulate their internal motivation, and provide residents with good primary health services.